The shared regulation in collaborative learning environments: A review of the state of empiric research - Juan Carlos CASTELLANOS RAMÍREZ; Javier ONRUBIA GOÑI (Ediciones Universidad de Salamanca, 2015)
Shared regulation processes occur within the feld of computer-supported collaborative learning as an emerging feld of study. Interest in this feld of study is justifed by assuming that regulatory processes positively affect the performance of groups and predict satisfactory results in student learning. This article reviews recent research about shared regulation processes in collaborative learning, both in face-to-face contexts and in virtual environments. To that end, prior to do the review, we discuss the importance of shared regulation on collaborative learning mediated by computer and, furthermore, we defne shared regulation and distinct it from other processes involved in collaborative learning, in particular from processes of construction of shared knowledge. We highlights, in the conclusions, a set of theoretical and empirical features that defne the shared regulation as a feld of study and, hereafter, guide future research focused on collaborative learning environments mediated by computer, as well as the design of support to encourage these processes.